City Branding of Marseille among International and Local Stakeholders - Zeidlerová, Michaela; San José Iglesias, Rafael; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis analyses the city branding of Marseille, focusing on two main aims: to examine city branding strategies implemented by city brand managers and to explore how the city is perceived by international and local stakeholders. Using a mixed-methods approach, the research combines semi-structured interviews with city branding professionals and an online survey among both local and international respondents. The study evaluated Marseille's branding strategies, as well as key brand elements, associations, identity, stakeholders, and media. The findings highlight both the strengths and challenges of Marseille's brand and underline the importance of aligning strategy with stakeholder perception. Based on the results, the thesis presents key conclusions and proposes targeted recommendations for improving Marseille's city branding efforts.
Vedoucí práce: Rafael San José Iglesias
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses